Everolimus Versus Mycophenolate Mofetil De Novo After Lung Transplantation: A Prospective, Randomized, Open‐Label Trial. Issue 11 (15th June 2016) - Strueber, M.; Warnecke, G.; Fuge, J.; Simon, A. R.; Zhang, R.; Welte, T.; Haverich, A.; Gottlieb, J.
Abstract : The role of mammalian target of rapamycin (mTOR) inhibitors in de novo immunosuppression after lung transplantation is not well defined. We compared Everolimus versus mycophenolate mofetil in an investigator‐initiated single‐center trial in Hannover, Germany. A total of 190 patients were randomly assigned 1:1 on day 28 posttransplantation to mycophenolate mofetil (MMF) or Everolimus combined with cyclosporine A (CsA) and steroids. Patients were followed up for 2 years. The primary endpoint was freedom from bronchiolitis obliterans syndrome (BOS). The secondary endpoints were incidence of acute rejections, infections, treatment failure and kidney function. BOS‐free survival in intention‐to‐treat (ITT) analysis was similar in both groups (p = 0.174). The study protocol was completed by 51% of enrolled patients. The per‐protocol analysis shows incidence of bronchiolitis obliterans syndrome (BOS): 1/43 in the Everolimus group and 8/54 in the MMF group (p = 0.041). Less biopsy‐proven acute rejection (AR) (p = 0.005), cytomegalovirus (CMV) antigenemia (p = 0.005) and lower respiratory tract infection (p = 0.003) and no leucopenia were seen in the Everolimus group. The glomerular filtration rate (GFR) decreased in both groups about 50% within 6 months. Due to a high withdrawal rate, the study was underpowered to prove a difference in BOS‐free survival. The dropout rate was more pronounced in the Everolimus group. Secondary endpoints indicate potential advantages of Everolimus‐based protocols but also a potentially higher rate of drug‐related serious adverse events. Abstract : Everolimus and mycophenolate mofetil have different adverse event profiles when used in de novo lung transplantation.